Pemanfaatan Google Business Profile Untuk Meningkatkan Akses UMKM Snack Dan Cemilan Nda Gemoy - F, Firmansyah; Meliyanti (Jurnal Pengabdian Masyarakat Tapis Berseri (JPMTB), 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in strengthening the national economy by contributing to community income and creating employment opportunities. However, many MSME owners still face challenges in marketing and utilizing digital technology, resulting in limited product recognition. Snack and Cemilan Nda Gemoy is a local culinary MSME that focuses on producing various types of snacks made from local ingredients with distinctive flavors and competitive quality. Despite its promising market potential, its promotional activities were previously limited to conventional methods such as direct selling and word-of-mouth marketing, which restricted consumer reach. Through the implementation of the Google Business Profile (GBP), a digitalization initiative was carried out by creating an official business profile on Google Search and Google Maps. The process included entering business identity information, uploading product photos, and providing training on independent account management to ensure consistent updates. The implementationresulted in improved business visibility, easier customer access to location and product information, and increased consumer trust through customer review features. The utilization of Google Business Profile has proven effective in helping Snack and Cemilan Nda Gemoy expand its market reach, strengthen its professional image, and adapt to the increasingly competitive digital business landscape.